Recruitment of catarina scallop Argopecten ventricosus larvae on artificial collectors off the NE coast of the Gulf of California - Soria, Rodrigo Gaspar (2013)
We evaluated recruitment of larvae of catarina scallop, Argopecten ventricosus, in the area of Puerto Peñasco, NE Gulf of California. We moored artificial collectors in 6 sites from June 2007 to August 2008 and replaced them every 2 months. We used monthly (July 2002-September 2011) sea surface temperature (SST, oC) and surface chlorophyll-a concentration (SSChl, mg m-3) Aqua/MODIS satellite data to describe seasonal environmental behavior study area. Also, we recorded bottom temperature at each site every 4 hours, and every two months measured sea surface salinity, temperature, and dissolved oxygen. We used a repeated measures ANOVA to evaluate differences in the number of recruited spat between main factors, and analyzed the presence of multimodal spat shell size frequency distributions. Overall, spat recruitment was negatively correlated with seawater temperature and showed higher spat recruitment abundances throughout winter, which is the season with the highest surface chlorophyll a concentration. We estimated multimodal shell size frequency distributions characterized by more than one modal size. The natural collection of A. ventricosus spat on artificial collectors in the area can be successfully performed over a protracted period (November-December to May-June). Our results extend the area where collection of A. ventricosus spat can be successful.